2020
DOI: 10.1074/jbc.ra120.012596
|View full text |Cite
|
Sign up to set email alerts
|

An astrocyte cell line that differentially propagates murine prions

Abstract: Prion diseases are fatal infectious neurodegenerative disorders in human and animals caused by misfolding of the cellular prion protein (PrPC) into the pathological isoform PrPSc. Elucidating the molecular and cellular mechanisms underlying prion propagation may help to develop disease interventions. Cell culture systems for prion propagation have greatly advanced molecular insights into prion biology, but translation of in vitro to in vivo findings is often disappointing. A wider range of cell culture systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…Astrocytes can replicate and accumulate PrP Sc independently of neurons [ 35 38 ]. Astrocytes were found to accumulate prions early, ahead of neuropathological changes involving vacuolation or neuronal loss [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes can replicate and accumulate PrP Sc independently of neurons [ 35 38 ]. Astrocytes were found to accumulate prions early, ahead of neuropathological changes involving vacuolation or neuronal loss [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, human-induced pluripotent stem cell (iPSC)-derived astrocytes have been successfully established to efficiently replicate human prions in a cell culture model [ 36 ]. An immortalized mouse astrocyte cell line could selectively and differentially propagate different murine prions [ 37 ]. Taken together, these results suggest that astrocytes play a critical role in prion propagation and pathogenesis.…”
Section: Neuroinflammation In Prion Diseasementioning
confidence: 99%
“…Additionally, Western blot showed much lower levels of PK-resistant PrP Sc in cells infected with RML as compared with 22L. However, real-time quaking-induced conversion (RT-QuIC) demonstrated that RML-infected cells had greater seeding activity than 22L-infected cells [ 44 ].…”
Section: Immortalized Cell Linesmentioning
confidence: 99%